EKSISTENSI PENDIDIKAN ISLAM PASCA REFORMASI - Wasehudin Wasehudin (Tarbawi, 2018)
The money crisis is a bitter history for the Indonesian nation, but in the end it can be diverse Law of National Education System Number 20 Year 2003 and Government Regulation Number 55 Year 2007 formally there is general education with Islamic education institute. This was reinforced after the Signing of a Joint Decree (SJD) of five ministers (Ministry of Education and Culture, Ministry of State Apparatus Empowerment and Bureaucracy Reform, Ministry of Home Affairs, Ministry of Finance and Ministry of Religious Affairs) should be a bright signal for the existence of institutional education in Indonesia Islamic education institutions, but unfortunately the fate of this joint decree together with the previous joint decree. Experts agree that education has a very important role in creating human resources as a determinant of the nation's future toward a just, prosperous and prosperous society. After the monetary crisis of 1997, the leaders of the Indonesian nation realized that education is an agent of change for the progress of a nation.